Endometrial receptivity tests in reproduction: a SWOT analysis - Juan A. Garcia-Velasco, MD, PhD; Joaquín Llácer, MD, PhD; Antonio Requena, MD, PhD; Miguel Ángel Checa, MD, PhD; José Bellver, MD, PhD; Ernesto Bosch, MD, PhD; Juan José Espinós, MD, PhD; Francisco Fabregues, MD, PhD; Ana Isabel Ortega, PharmD, PhD; Juan Fontes, MD, PhD (AJOG Global Reports, 2023)
Endometrial receptivity and its management in assisted reproduction is now a significant focus of research interest. Endometrial receptivity tests, which analyze different panels of gene expression, are usually offered in fertility clinics to determine the women's individual ‘window of implantation’, providing a personalized timing for embryo transfer. However, there are still no definite indications on whether its inclusion in the study of the infertile couple or the study of patients with repeated implantation failure is essential.